A clinician survey for management of the secondary immunodeficiency caused by hematological malignancies in China. Issue 3 (22nd January 2021) - Ye, Chunmei; Liu, Juan; Song, Xiaolu; Zheng, Sujie; Liu, Jinlin
Abstract : Abstract: Unlike Western countries, there are still few clinical immunology specialists in China, and the optimal care for secondary immunodeficiency caused by hematological malignancies is unknown. Therefore, we initiated this clinician survey study to describe the current situation of the care for malignancy patients with hypogammaglobulinemia in China. We adapted a previously published online questionnaire of current clinical practices regarding the management of secondary immunodeficiency caused by hematological malignancies and then distributed the questionnaire to 52 hematologists in China via WeChat mobile software; the survey collected demographic details, starting dosage, target immunoglobulin (Ig) level, monitoring, criteria for stopping Ig replacement, vaccination use, and oral antibiotic prophylaxis for hypogammaglobulinemia patients. Forty-eight hematologists responded. 28(58.33%) respondents had more than 10 years of experience. Nevertheless, 40(83.33%) respondents reported that they did not use any specific criteria for prophylactic Ig replacement in hypogammaglobulinemia patients. However, 27(56.25%) respondents reported that they had used intravenous immunoglobulin (IVIG); however, the starting dose, frequency, and target Ig level were significantly varied. Additionally, the criteria for stopping Ig replacement were significantly varied. Only one respondent (2.08%) used subcutaneous immunoglobulin (SCIG). Moreover, 35(72.92%) respondents reported no vaccination prior to Ig replacement, and 47(97.92%) respondents reported that they had not used antibiotic prophylaxis in secondary hypogammaglobulinemia patients. Official guideline for the care for secondary immunodeficiency (SID) of the hematological malignancies patients should be issued in China, and significant attention of the hematologists should be paid to the use of prophylactic antibiotics and Ig replacement for the care of patients with hypogammaglobulinemia caused by hematological malignancies, as these agents could significantly reduce the infection rate in China. Abstract : Supplemental Digital Content is available in the text